Proteomic characterisation and phylogenetic derivation of ovine αS1-CN B and αS1-CN G genetic variants. (August 2022) - De Pascale, Sabrina; Caira, Simonetta; Garro, Giuseppina; Mauriello, Rosalba; Scaloni, Andrea; Cosenza, Gianfranco; Chianese, Lina
Abstract: A combination of chromatographic, immunoelectrophoretic and mass spectrometric methods was applied to healthy individual milk of ovine massese breed. Caseome of αS1 -casein (αS1 -CN) fraction was characterised in homozygous and heterozygous phenotypes for the novel B and G genetic variants. Using ovine αS1 -CN C counterpart as reference, amino acid substitutions and phosphorylated components were determined. The replacement of p.Arg90>His and p.Ile194>Thr were found in αS1 -CN B variant, while the single p.Ile194>Thr substitution occurred in αS1 -CN G variant. The quali-quantitative composition of phosphorylated αS1 -CN components in milk of animals bearing each variant was defined, highlighting possible genetic markers for assessment of dairy product quality. The heterogeneity of the electrophoretic profiles of the corresponding caseomes was due to the number of phosphorylated components and their net charge and pI values, and updated the ovine αS1 -CN phylogenetic tree, suggesting αS1 -CN G as the ancestral variant of αS1 -CN B and other variants.